2008
DOI: 10.1152/ajplung.00445.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of sphingosine kinase inhibitor attenuates airway inflammation in asthmatic mouse model

Abstract: Sphingosine 1-phosphate (S1P) produced by sphingosine kinase (SPHK) is implicated in acute immunoresponses, however, mechanisms of SPHK/S1P signaling in the pathogenesis of bronchial asthma are poorly understood. In this study, we hypothesized that SPHK inhibition could ameliorate lung inflammation in ovalbumin (OVA)-challenged mouse lungs. Six- to eight-week-old C57BL/6J mice were sensitized and exposed to OVA for 3 consecutive days. Twenty-four hours later, mice lungs and bronchoalveolar lavage (BAL) fluid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 40 publications
4
96
0
Order By: Relevance
“…Interestingly, S1P, normalized to the BALF protein concentration (37.5 6 3.4 mg/ml in WT mice; 41.1 6 2.9 mg/ml in CF mice), was decreased in CF BALF (P , 0.01; Figure 6). These concentrations are comparable to those analyzed previously in the BALF of C57BL/6 mice by an enzymatic method and thin liquid chromatography (24,25).…”
Section: Cf Pulmonary Milieu Affects Maturation and Activation Of Dcssupporting
confidence: 88%
“…Interestingly, S1P, normalized to the BALF protein concentration (37.5 6 3.4 mg/ml in WT mice; 41.1 6 2.9 mg/ml in CF mice), was decreased in CF BALF (P , 0.01; Figure 6). These concentrations are comparable to those analyzed previously in the BALF of C57BL/6 mice by an enzymatic method and thin liquid chromatography (24,25).…”
Section: Cf Pulmonary Milieu Affects Maturation and Activation Of Dcssupporting
confidence: 88%
“…The systemic treatments with SKI-II had no effect on the infiltration of inflammatory cells (D). (12), N,N-dimethylsphingosine (DMS) (11,35), and 2-(p-hydroxyanilino)-4-(p-chlorophenyl) thiazole (SK-I) (11). The in vivo AHR induced by antigen challenge was also attenuated in the sphingosine kinase-1 knockout mice (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sphingosine kinase inhibitors such as DMS (11,35) and SK-I (11) could attenuate antigen-induced airway inflammation. However, in the present study, the SKI-II treatments had no significant effect on the increase in BAL cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies linking asthma to sphingolipids have been centered on inflammatory and allergic mechanisms related to the sphingolipid mediator S1P (48)(49)(50)(51)(52)(53). S1P is involved in mast cell degranulation and airway hyperresponsiveness in allergic asthma models (53)(54)(55)(56) and has been a focus on the development of sphingolipid-based anti-inflammatory agents (51,(57)(58)(59).…”
Section: Ormdl3 and Sphingolipidsmentioning
confidence: 99%